Risk analysis of tillage and crop rotation alternatives with winter wheat for south central Kansas - Pachta, Matthew J. (Kansas State University, 2010)
This study examines the economic profitability of reduced-tillage and no-tillage systems for corn, soybeans, and grain sorghum production in annual rotation with winter wheat, and monoculture wheat and grain sorghum in south-central Kansas. Net returns to land and management per acre for each of 13 production systems are calculated several different ways. Net returns are calculated using the 10-year average yield for each crop, the average crop price from 2009, and 2009 input prices. A distribution of net returns is also calculated using the actual historical yields and crop prices from 1997 to 2006 and 2009 input prices. This process is repeated, except average crop prices from 2006, 2007, 2008 and 2009 are now used. Finally, net returns are calculated using simulated yield and price distributions based on actual historical yields, four historical monthly price series, and 2009 input costs. Overall, the reduced-tillage wheat-soybean systems (RTWS) have the greatest net returns for each of the net return distributions. No-tillage wheat-soybean (NTWS) generally has the second highest net returns. Stochastic Efficiency with Respect to a Function (SERF) is used to determine the preferred management strategies under various risk preferences. SERF analysis indicates that RTWS is the system most preferred by all producers, regardless of their level of risk aversion. NTWS is typically the second most preferred system to RTWS. Using historical annual prices for 1997 to 2006 and the simulated monthly prices series for 2006 to 2009 and 2007 to 2009 to calculate the net return distributions, managers with higher levels of risk aversion prefer reduced-tillage wheat-grain sorghum (RTWG) over no-tillage wheat-soybean (NTWS). Sensitivity analysis shows that as the price of glyphosate falls, no-till systems become relatively more profitable. SERF analysis using the historic yields, 2006 to 2009 simulated monthly prices, and 2009 input costs with reduced glyphosate prices indicate that NTWS would be the system most preferred by producers at all levels of risk aversion. RTWS closely follows NTWS as the next preferred system with those conditions also for all levels of risk aversion.
Keywords: Crop Rotation; Tillage; Risk; SERF; No-tillage; Reduced-tillage; Agriculture, Agronomy (0285); Economics, Agricultural (0503)